A Multilevel Model of Teachers’ Job Performance: Understanding the Effects of Trait Emotional Intelligence, Job Satisfaction, and Organizational Trust - Li, Mingwei; Pérez-Díaz, Pablo Alejandro; Mao, Yaqing; Petrides, K. V. (Frontiers in Psychology, 2018)
Research on the role of trait emotional intelligence (trait EI; Petrides, 2001) relating to teaching performance has emerged as an important topic. The present study proposes a multilevel model of teachers’ trait EI in relation to their job performance, which simultaneously addresses the mediating role of job satisfaction and the influences of school-level factors (i.e., organizational trust and principals’ trait EI). Results from a sample of 881 teachers and thirty-seven principals in Chinese primary schools showed that job satisfaction partially mediated the positive relationship between teachers’ trait EI and their job performance. In addition, the findings demonstrated a cross-level moderated mediating effect, with the indirect effect of teachers’ trait EI on job performance (via job satisfaction) becoming stronger for teachers working in schools with lower levels of organizational trust. The hypothesized role of principals’ trait EI on teachers’ job performance was not supported. The theoretical and practical implications of these findings are discussed.